HUBUNGAN PENGETAHUAN DAN SIKAP REMAJA PUTRI TENTANG VULVA HYGIENE DENGAN TINDAKAN PENCEGAHAN KEPUTIHAN - Zalni, Rummy Islami (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
leucorrhoea is a very common symptom experienced by most women. Data research on reproductive health, 75% of women in the world must be having a leucorrhoea least once in their lifetime and 45% of them could experience it twice (Pribakti, 2011). While in Indonesia, at least 90% of women in Indonesia has the potential to develop a leucorrhoea, including young women (ditto, 2011). The purpose of this study was to determine the related knowledge and attitude of young women of vulva hygiene with practices of prevention of leucorrhoea at vocational school kansai pekanbaru. This type of research is descriptive analytic, conducted at vocational school Kansai Pekanbaru on 27 July - 4 August 2015, with a total population of 307 students in the sample studied totaled 75 students. Instruments in research that using a questionnaire. The sampling technique by simple random sampling. Manual processing and data analysis and bivariate frequency distribution using Chi-square test. The result showed 46 people (61.3%) knowledgeable enough about vulvar hygiene, as many as 40 people (53.3%), being negative and as many as 43 people (57.3%) who had a bad whitish precautions. The relationship between knowledge and action with p value 0,000 < 0.05? and the relationship between attitudes and actions with p value 0,000 < 0.05? Expected to young women in vocational Kansai Pekanbaru increase knowledge so that respondents can prevent and provide information to families about the cleanliness of the external genitals with vaginal discharge precautions.